RELATION BETWEEN CONFLICT RESOLUTION AND SOCIOMETRIC STATUS IN EARLY ELEMENTARY PRIMARY SCHOOLCHILDREN - Dovydaitienė, Miglė; Platkevičiūtė, Vaida (Acta Paedagogica Vilnensia, 2014)
The ability to resolve conflicts is an important part of social competence during early elementary school years. Children who can resolve conflicts have a greater possibility of being accepted by their peers, whereas children who make poor choices when resolving conflicts are likely to be rejected by their peers (Kupersmidt, Dodge, 2004). Conflict resolution is unavoidable part of communication, and the lack of conflict solving skills could be related to negative consequences of a person’s social adjustment in the school peer group. When analyzing the literature, let us to presume that both the ways of solving conflict situations and the adjustment to the peer group are important factors related to the social development and adaptation of early school age children. The conflict behavior of a child is one of the factors that permit a child to reveal his/her capacities and inner features which could be either accepted or rejected by the contemporaries.The aim of this research was to evaluate the ways of solving conflicts chosen by early school age children and its relation with children’s sociometric status in the group. In the research, 142 children, 168 parents, and 142 schoolteachers took part. We created a method to evaluate the ways of resolving conflicts. The method consists of a structural interview with children and a questionnaire for teachers and parents. The children were provided with pictures illustrating conflict situations. The child status in the group was measured using the sociometrical method suggested and improved by D. Moreno.The results have revealed that early school age children more often choose accommodation and self-interest assertion in order to solve a conflict. Middle- status children, more often than those of another status, choose accommodation and more seldom self-interest assertion. Children having a leader status in the group more often than other children, choose accommodation in order to solve conflicts. Also, the ways of solving conflicts differ in the groups depending on age and sex.
Keywords: early elementary primary schoolchildren; conflict; conflict resolution strategy; group status